Kratom (Mitragyna speciosa): Medicinal Marvel or Menace? Assessing Potency, Risk, and Future Prospect of Herbal Medicine - Ni'ma, Neli Syahida (Indonesian Journal of Chemical Science, 2024)
Kratom (Mitragyna speciosa) boasts a rich historical legacy as an herbal plant employed across generations for diverse therapeutic purposes, including pain relief, inflammation mitigation, anti-diarrheal effects, cough suppression, alleviation of fatigue, and anti-anxiety and antidepressant properties. Despite its acclaimed medicinal versatility, this plant harbors psychoactive attributes, thereby posing the risk of misuse and potential dependence, along with withdrawal effects. The alkaloid composition of kratom, featuring opioid receptor agonist properties, underscores its analgesic efficacy, thereby carrying a risk of dependence and withdrawal akin to other opioid agonists. Beyond its role as an opioid agonist, the analgesic mechanism of kratom extends to additional complementary pathways, presenting a potential superiority to morphine. Notably, kratom constituents inhibit key drug-metabolizing enzymes (CYP) and the multidrug transporter, p-glycoprotein, potentially leading to heightened levels of co-administered drugs that are substrates for these proteins, presenting a potential risk of adverse outcomes, including fatality. Given the perceived imbalance of risks versus benefits, there arises a rationale for the prohibition of kratom use as an herbal remedy. However, the exploration of purified drugs derived from kratom isolates remains a promising avenue for research, with the potential to surpass standard pharmaceutical interventions.